Synthesis, characterization and photophysical studies of a novel polycyclic diborane - Yao, Chang-Jiang (2021)
Treatment of tetrakis(dimethylamino)diboron (B₂(NMe₂)₄) with 1,4-bis (2-(triisopropylsilyl)ethynyl)naphthalene-2,3-diamine (1) generated a large NBBN polycyclic compound 1,1-B₂{2,3-(NH)₂ -1,4-(ⁱPr₃ SiC₂)₂C₁₀H₄} (2). The X-ray structure analysis reveals that 2 has a twisted structure (dihedral angle ≈ 21.75°) with a rather short B-B bond (1.667(9) Å). Theoretical calculations on 1,1-B₂ isomer 2 and its counterpart 1,2-B₂ isomer 3 have been conducted to understand their frontier orbital energy levels. Compound 2 shows strong emission with a high quantum yield of 0.52, despite the presence of many unbeneficial non-radiative behaviors such as the vibration of the TIPS groups and the rotation of the B-B single bond.